The hidden curriculum of digital peer interaction: a multisite ethnography in online higher education - Eka Ariyati; Zulfariati; Bernardus Agus Rukiyanto; Aliah Bagus Purwakania Hasan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Peer interaction in Digital Learning Environments (DLEs) is commonly treated as supplementary to online instruction, yet it can function as a key site where hidden curriculum is enacted through informal socialization. This study examines how peer-to-peer interaction transmits, negotiates, and reinterprets unwritten norms that shape students’ academic identities and participation practices in online higher education. Using a multisite ethnographic case study grounded in sociocultural theory and critical pedagogy, data were collected over three months from three Indonesian higher education institutions using synchronous and asynchronous digital platforms. Participants included 36 students and 6 lecturers. Data comprised virtual classroom observations, online discussion forum archives, and semi-structured interviews, and were analyzed using thematic analysis supported by NVivo 12. Findings indicate that peer interaction generated four clusters of hidden curriculum: (1) digital ethics enacted through peer regulation of communication tone, response timing, and visibility practices that shaped credibility and participation; (2) academic integrity negotiated through peer-shared strategies that blurred boundaries between mutual support and misconduct; (3) emotional work expressed in affective labor to sustain group harmony and minimize conflict-related sanctions; and (4) hidden hierarchies produced by unequal platform literacy and social capital, positioning certain students as informal gatekeepers of information and belonging. These peer-mediated norms operated as forms of governance outside formal course design, shaping participation strategies, sense of belonging, and academic identity construction. The study offers context-specific evidence from Indonesian online higher education and highlights the importance of critical digital pedagogy that renders implicit norms discussable and supports more inclusive online learning practice.